Pengaruh Pendidikan Kesehatan Terhadap Tingkat Pengetahuan Pelajar SMA Tentang HIV/AIDS - Harmawati, Harmawati; Sari, Desriza Artika; Verini, Devi (Jurnal Endurance, 2018)
Solok district Health Department until November 2016 has log as many as 30 cases of AIDS with the number of death 16 cases. The area of Subdistrict Lembang jaya from 2012 until 2015 there are 5 positive AIDS cases and deaths by as much as 3 cases. The purpose of the reseach is to know the infuence of helath education toward high school students knowledge level about HIV/AIDS in high school 02 sub district of Lembang JayaSolok Regency in 2017. This research type was Pre Experimental design with One Group Pretest-Posttest Design. This research was conducted from Desember 2016 until February 2017 of 18 respondents. Data retrieval is performed using question form and data prossesing with computer and the test statistic used is the test of Wilxocon with a value of p =0,05. The results showed the averge level knowledge students of HIV/AIDS before it was given heslth education that is 8,44 and level knowledge students of HIV/AIDS after given health education that is 11.89. The influence of health on the level of knowledge high school student obtained value p-value = 0,000. The conclusion of the results of the research there is the influence of health education toward high school students knowledge a bout HIV/IDS in high school 02 sub district of Lembang Jaya Solok Regency in 2017. Advice : for the school to optimize program in an effort to improve knowledge students to get the information health HIV/AIDS to have a partnership with health center.Dinas Kesehatan Kabupaten Solok hingga bulan November 2016 telah mendata sebanyak 30 kasus AIDS dengan angka kematiannya 16 kasus. Daerah Kecamatan Lembah Jaya dari tahun  2012 hingga tahun 2015 terdapat 5 kasus positif AIDS, yang meninggal sebanyak 3 kasus. Tujuan penelitian adalah untuk mengetahui pengaruh pendidikan kesehatan terhadap tingkat pengetahuan pelajar SMA tentang HIV/AIDS di SMA 02Kecamatan Lembang JayaKabupaten Solok tahun 2017.Penelitian ini  Pre Eksperimental dengan rancangan One Group Pre test – Post test Design.Penelitian ini dilakukan dari bulan Desember 2016 sampai Februari 2017 terhadap 18 responden Pengambilan data dilakukan dengan digunakan adalah uji Wilxcoxon  dengan nilai p=0,05. Hasil penelitian diperoleh rata-rata tingkat pengetahuan pelajar tentang HIV/AIDS sebelum diberikan pendidikan kesehatan 8,44 dan rata-rata tingkat pengetahuan sesudah diberikan pedidikan kesehatan yaitu 11,89.Ada pengaruh pendidikan kesehatan terhadap tingkat pengetahuan pelajar SMA dengan nilai p-value = 0,000. Simpulan hasil penelitian ini menunjukkan  ada pengaruh pendidikan kesehatan terhadap tingkat pengetahuan pelajar SMA tentang HIV/AIDS di SMA 02 Kecamatan Lembang Jaya Kabupaten Solok Tahun 2017. Pihak sekolah untuk lebih mendukung  program dalam meningkatkan pengetahuan pelajar untuk mendapatkan informasi kesehatan tentang HIV/AIDS dengan melakukan kerja sama dengan pihak Puskesmas.